A Proposed Design of Ketapang Fruit Breaker Tool: Proposed Design of Ketapang Fruit Breaker Tool - Rismawati, Rismawati; Thitin Binalopa (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2024)
Based on research from experiments carried out, the use of a ketapang fruit breaker design tool is more efficient than a simple cracker. The approach used is by technical analysis and the stages of tool design, including: (1) The design stage, namely the stage that identifies consumer needs, the specifications of the design tool and the preparation of concepts using the goal tree method and function analysis (2) Concept Design, which is the stage regarding the functional and structural design in the design of the ketapang fruit breaker (3) The performance of the ketapang fruit breaker is the testing of the results of the fruit breaker design Ketapang with a comparison of existing simple tools, where the efficiency level reaches 20%. Keywords: Ketapang Fruit, Tool Design, Efficiency